Deep space debris—Detection of potentially hazardous asteroids and objects from the southern hemisphere - Kruzins, Ed; Benner, Lance; Boyce, Russell; Brown, Melrose; Coward, David; Darwell, Sam; Edwards, Phil; Elizabeth-Glina, Lauren; Giorgini, Jon; Horiuchi, Shinji; Lambert, Andrew; Lazio, Joseph; et al. (Frontiers in Space Technologies, 2023)
Space debris are composed of both natural and human made objects, some in near Earth orbits while others are passing through deep space. Asteroids may represent one form of near Earth and deep space debris. In this article we report on a set of asteroid observations from the southern hemisphere. We indicate that Apollo and Aten class asteroids represent another form of deep space debris of a potentially hazardous nature to orbiting spacecraft and/or Earth based locations. We also show some of the operational challenges, types of facilities and the importance of geographic diversity, that is, necessary for detecting, observing and characterising asteroids, especially PHA’s. For many years, space agencies and institutions have observed and monitored near Earth asteroids and objects (NEO’s) using high gain radio frequency antennas and optical telescopes in the northern hemisphere (GSSR, Arecibo, Catalina, Pan-STARRS, Atlas and Linear) 1) However a regular operational system to monitor the southern skies does not have the same level of maturity and is where a percentage of asteroids and various human made objects are not detected until they pass into northern skies. To fill that gap the Southern Hemisphere Asteroid Radar Program (SHARP) 2) located in Australia uses available antenna time on either a 70 or 34 m beam waveguide antenna located at the Canberra Deep Space Communication Complex (CDSCC) to transmit a Doppler compensated continuous radio wave at 2.114 GHz (14.2 cm) and 7.15945 GHz (4.2 cm) toward the NEO and receive its echoes at the 64 m Parkes or 6 m × 22 m Australia Telescope Compact Array (ATCA) antennas at Narrabri in Australia. This mode of NEO observation is termed a deep space bistatic radar. The southern hemisphere program has also recently been joined by the 12 m University of Tasmania antennas at Hobart (Tasmania) and Katherine (Northern Territory). Combining SHARPS bistatic radar with small optical apertures located at the University of New South Wales (UNSW) and University of Western Australia (UWA) allows combined optical/RF NEO detections. Whilst sub-metre class optical instruments have contributed independently to asteroid detection over decades, the use of coordinated small 0.3–0.5 m instruments synchronized to large asteroid radars offers an observational flexibility and adaptability when larger optical systems 3) are dedicated to other forms of professional optical astronomy. Since 2015, SHARP has illuminated and tracked over 30 NEO’s ranging in diameter from 7 to 5000 m at ranges of 0.1–18 lunar distances (LD) from Australia.